Production of negative hydrogen ions within MMS Fast Plasma Investigation due to solar wind bombardment - Gingell,IL; Schwartz,SJ; Gershman,DJ; Paterson,WR; Desai,RT; Giles,BL; Pollock,CJ; Avanov,LA (Journal of Geophysical Research: Space Physics, 2018)
The particle data delivered by Fast Plasma Investigation (FPI) instrument aboard NASA's Magnetospheric Multiscale (MMS) mission allows for exceptionally high-resolution examination of the electron and ion phase space in the near-Earth plasma environment. It is necessary to identify populations which originate from instrumental effects. Using FPI's Dual Electron Spectrometers (DES) we isolate a high energy (~keV) beam, present while the spacecraft are in the solar wind, which exhibits an azimuthal drift with period associated with the spacecraft spin. We show that this population is consistent with negative hydrogen ions H- generated by a double charge exchange interaction between the incident solar wind H+ ions and the metallic surfaces within the instrument. This interaction is likely to occur at the deflector plates close to the instrument aperture. The H- density is shown to be approximately 0.2-0.4% of the solar wind ion density, and the energy of the negative ion population is shown to be 70% of the incident solar wind energy. These negative ions may introduce errors in electron velocity moments on the order of 0.2-0.4% of the solar wind velocity, and significantly higher errors in the electron temperature.